2007
DOI: 10.1007/s00134-007-0672-5
|View full text |Cite|
|
Sign up to set email alerts
|

Invasive candidiasis in pediatric intensive care patients: epidemiology, risk factors, management, and outcome

Abstract: Prompt removal of lines and initiation of antifungal treatment are the milestones of management. Conventional amphotericin B remains a commonly used antifungal agent, but its lipid formulations and fluconazole are also used frequently. Novel antifungal agents such as second-generation triazoles and echinocandins exhibit potential as alternative agents in critically ill children with ICI. Although response rates are still far from satisfactory, improved understanding of risk factors, preventive strategies and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 89 publications
2
88
1
9
Order By: Relevance
“…Admission to PICU from inpatient ward, ETT and MV were also associated with candidemia in general, higher NAC than CA, and increased risk for mortality (Tables 1,3,4). Few studies have compared the risk factors between patients with CA and NAC BSI in the non-neonatal pediatric population and found no difference in the risk factors between patients with CA and NAC BSI [5,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Admission to PICU from inpatient ward, ETT and MV were also associated with candidemia in general, higher NAC than CA, and increased risk for mortality (Tables 1,3,4). Few studies have compared the risk factors between patients with CA and NAC BSI in the non-neonatal pediatric population and found no difference in the risk factors between patients with CA and NAC BSI [5,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing role of non-albicans Candida (NAC) species, some of which are intrinsically or potentially resistant to antifungal agents, has been observed. NAC species, particularly C. parapsilosis and C. tropicalis, account for almost half of invasive Candida infections in pediatric patients [4,5]. Nonalbicans Candida became more frequent causative agents for invasive fungal infections in the ICU with high transmission of C. parapsilosis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the magnitude of damage, disease ensues, which can be acute and/or recurrent in nature (4,(17)(18)(19). As a result, C. albicans infections are recognized as a serious public health challenge with high clinical and socioeconomic importance, representing one of the most prevalent agents identified in nosocomial infections (10,20,21).…”
Section: Candida Albicans: a Versatile Fungal Pathogenmentioning
confidence: 99%
“…1 Among them, Candida species have been the dominant type representing the majority of blood stream infections (BSI) and associated catheter-related BSI with a rate of 10%. 2 Recent studies have reported increased incidences of other Candida species, especially Candida parapsilosis besides Candida tropicalis and Candida glabrata.…”
Section: Introductionmentioning
confidence: 99%